Transformation of Regional Revenue and Fiscal Independence of Regency/City of NTB 2012-2021 - Fathurrahman (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
This study aims to analyze the transformation of regional revenue structures and their implications on the fiscal independence of districts/cities in West Nusa Tenggara Province during the period 2012–2021. The main issue studied is whether the increase in Regional Original Revenue really reflects the strengthening of fiscal independence or only shows nominal growth that has not been able to shift the dominance of central transfers. The study uses a descriptive-analytical quantitative approach based on secondary data from Local Government Financial Statements in 10 districts/cities in NTB. The analysis is focused on four main components of revenue, namely Regional Original Revenue, Revenue Sharing Fund, General Allocation Fund, and Special Allocation Fund. Analysis techniques include growth calculations, compound annual growth rates, PAD contributions, transfer dependency ratios, and the preparation of regional fiscal typologies. The results show that the aggregate PAD increased from around Rp571.82 billion in 2012 to around Rp1.98 trillion in 2021, with a CAGR of 14.82 percent per year. However, in 2021 PAD's contribution to the main revenue structure only reached 17.20 percent, while central transfers still dominated at 82.80 percent. These findings suggest that PAD growth has not fully reflected substantive fiscal independence. Fiscal typology shows variations between regions, with Mataram City being relatively stronger, some districts in transitional positions, and some regions still experiencing high transfer dependence. This study emphasizes that fiscal independence needs to be assessed through changes in revenue structure, not just an increase in the nominal PAD, so that it can be the basis for a fairer, more realistic, and sustainable regional fiscal policy.